A spatial coupling model to study dynamic performance of pantograph-catenary with vehicle-track excitation. (April 2021) - Song, Yang; Wang, Zhiwei; Liu, Zhigang; Wang, Ruichen
Abstract: In the high-speed railway industry, the pantograph-catenary system is responsible to provide continuous electric energy for the high-speed train. The pantograph-catenary system suffers multiple impacts from the complex work environment. The vehicle-track excitation is one of the normal disturbances to the pantograph-catenary interaction. Previous studies only consider the vertical effect of the vehicle-track vibration on the pantograph-catenary interaction. To address this deficiency, both of the pantograph-catenary and vehicle-track models are constructed in this paper. The validations of both models are verified by the experimental test and the world benchmark, respectively. The pantograph base follows the translations and rotations of the car-body caused by random rail irregularities. In combination with a spatial contact model between the contact wire and the pantograph strip, the spatial vibration of the carbody can be fully considered in the pantograph-catenary interaction. The statistical analysis, stochastic analysis and frequency analysis are performed to make sense of the effect of the random track irregularities on the pantograph-catenary interaction. The deviation of the contact point away from the strip centre caused by the carbody vibration is also analysed. The results show that the reliability of the pantograph-catenary system shows a continuous decrease in the degradation of rail quality. The carbody vibration may cause the de-wirement of the pantograph in extreme conditions. Finally, an application example is given to evaluate the dynamic performance of the pantograph-catenary system running on the China high-speed network with realistic rail irregularities.